2003
DOI: 10.1002/jclp.10223
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between coping style and PAI profiles in a community sample1

Abstract: Relationships between coping style and psychological functioning were examined in a heterogeneous community sample (N = 168). Psychological functioning was categorized with the Personality Assessment Inventory (PAI; Morey, 1991). Subjects were assigned to PAI configurai profile clusters, using T‐scores from PAI clinical scales. Three PAI clusters were prominent in this sample: normal, anxious, and eccentric. Multivariate analysis of covariance revealed that these clusters differed significantly in coping style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Persons scoring high on trait anxiety in general are more anxious. As a result, high-scorers will presumably seek more support from significant others [24]. However, Hobson et al [25] found that persons scoring high on trait anxiety tend to score lower on perceived social support compared with persons scoring low on trait anxiety.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Persons scoring high on trait anxiety in general are more anxious. As a result, high-scorers will presumably seek more support from significant others [24]. However, Hobson et al [25] found that persons scoring high on trait anxiety tend to score lower on perceived social support compared with persons scoring low on trait anxiety.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, women who were not treated yet and scored low on dispositional optimism experienced more cancer-specific distress. Persons high on trait anxiety were inclined to seek more support from others, while they also tended to be dissatisfied with the received social support [24,25]. Several studies found that network size decreased due to fatigue [26,27] or to the fact that persons were due to their illness less able to provide support to their social network, which caused an imbalance between the amount of support given to others and the amount of help received by the network [18].…”
Section: Introductionmentioning
confidence: 95%
“…The literature is mixed in terms of using the multiple individual scales in analyses or using factor scores that combine the various scales into a few general coping styles (Carver et al, 1989;Deisinger, Cassisi, & Whitaker, 1996). Taking into account both factor analyses from previous studies and current theory on stress and coping, the scales were divided into three composites, with higher scores on the composite indicating greater use of that particular type of coping.…”
Section: Methodsmentioning
confidence: 99%
“…The PAI has been successfully used to assess borderline psychopathology and diagnosis in a variety of populations and settings (Bagge et al, 2005;Deisinger, Cassisi, & Whitaker, 2003;Evershed, Tennant, & Boomer, 2003;Trull, 1995). The clinical scale measuring BPD symptomatology is composed of a 24-item full scale (Borderline [BOR]) with four subscales: Affective Instability (BOR-A; e.g., ''My mood can shift quite suddenly''), Identity Disturbance (BOR-I; ''Sometimes I feel terribly empty inside''), Negative Relationships (BOR-N; ''My relationships have been stormy''), and Self-Harm (BOR-S; ''When I'm upset I typically do something to hurt myself'').…”
Section: Instrumentsmentioning
confidence: 99%